Vibration Analysis of the Flexible Beam Using Dynamic Solver K_Sim - Park, Dongil; Kim, Doohyung (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2015)
We developed the dynamic solver including the pre-processor with GUI, kinematic/dynamic solver and the post-processor. This can support to analyze the flexible body dynamics as well as the rigid body dynamics. Because almost robot system has the multi bodies including some flexible bodies, multi flexible body dynamics is very important. In the paper, we carried out the vibration analysis of the flexible beam using the developed dynamic solver K_Sim and compared it to the commercial multi flexible body dynamic solver.